Effect of posture change on the geometric features of the healthy carotid bifurcation - Aristokleous, Nicolas; Seimenis, Ioannis; Anayiotos, Andreas (My University, 2011)
Segmented cross-sectional MRI images were used to construct 3-D virtual models of the carotid bifurcation in ten healthy volunteers. Geometric features, such as bifurcation angle, internal carotid artery (ICA) angle, planarity angle, asymmetry angle, tortuosity, curvature, bifurcation area ratio, ICA/common carotid artery (CCA), external carotid artery (ECA)/CCA, and ECA/ICA diameter ratios, were calculated for both carotids in two head postures: 1) the supine neutral position; and 2) the prone sleeping position with head rotation to the right (∼80°). The results obtained have shown that head rotation causes 1) significant variations in bifurcation angle [32% mean increase for the right carotid (RC) and 21% mean decrease for the left carotid (LC)] and internal carotid artery angle (97% mean increase for the RC, 43% mean decrease for the LC); 2) a slight increase in planarity and asymmetry angles for both RC and LC; 3) minor and variable curvature changes for the CCA and for the branches; 4) slight tortuosity changes for the braches but not for the CCA; and 5) unsubstantial alterations in area and diameter ratios (percentage changes < 10). The significant geometric changes observed in most subjects with head posture may also cause significant changes in bifurcation hemodynamics and warrant future investigation of the hemodynamic parameters related to the development of atherosclerotic disease such as low oscillating wall shear stress and particle residence times.
Keywords: Carotid bifurcation; Image-based CFD; Medical imaging; Posture changes